2012
DOI: 10.46743/1540-580x/2012.1384
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Academic Motivations in Allied Health Classes

Abstract: Purpose: Human Anatomy & Physiology [HAP] courses are considered “difficult” by both faculty and students, and many students fail to pass the courses. An attempt was made to understand how students’ academic motivations may contribute to their success or failure in these courses. Method: The project used a non-experimental design with a convenience sample. Students in five sections of HAP I and HAP II were invited to complete an anonymous 42-item questionnaire that included an adapted version of the Academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
1
13
1
1
Order By: Relevance
“…Aside from these findings, Khalaila [14] studied the academic motivation of undergraduate nursing students and reported students perceiving themselves as academically competent with higher GPAs. The literature has reported a positive correlation between academic motivation and academic success, as reflected by the GPA [13,[15][16]. However, no similar finding was found in the present study.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Aside from these findings, Khalaila [14] studied the academic motivation of undergraduate nursing students and reported students perceiving themselves as academically competent with higher GPAs. The literature has reported a positive correlation between academic motivation and academic success, as reflected by the GPA [13,[15][16]. However, no similar finding was found in the present study.…”
Section: Discussioncontrasting
confidence: 73%
“…It also examined the relationships between student characteristics and academic motivation, including sex, academic year, and GPA, which pointed out predictors as shown in the results. The results revealed that academic motivation among students in Jordanian universities is below reported levels in many international literature [5,13]. These results include the AMS and its seven subscales, constituting three domains (i.e., intrinsic, extrinsic motivation, and motivation).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Behaviors motivated by external regulation occur because of an external acting influence, such as satisfying an external demand or obtaining an externally imposed reward contingency. SDT has been used to understand the correlation between academic motivation and other variables such as curiosity, academic persistence, learning attitude, and academic performance in the education field (Maurer et al, 2013; Vasconcellos et al, 2020). Systematic review and meta‐analysis research (e.g., Locke & Schattke, 2019; Richardson et al, 2012) highlighted the significant influences of intrinsic motivation and extrinsic motivation on academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…As Silva et al show (2018), since 1989, the year in which the AMS was developed, it has been applied with all kinds of audiences, including university students (Núñez Alonso et al, 2005;Guay et al, 2015) in courses in different areas, such as psychology (Cokley et al, 2001;Ramos, 2013), business (Smith et al, 2010), dentistry (Orsini, Evans, Binnie, Ledezma & Fuentes, 2016), physical education (Spittle et al, 2009), mathematics, physics and nutrition (Sturges, Maurer, Allen, Gatch & Shankar, 2016;Maurer et al, 2012;Lim & Chapman, 2015), among others. From all these evidences, it might be assumed that this scale is adaptable to any field of knowledge (Silva et al, 2018).…”
Section: The Motivational Questionnairementioning
confidence: 99%